Neoadjuvant chemotherapy for Ewing's sarcoma family tumors of the uterine cervix: A case report - Masahiko Mori; Kazunori Honda; Hirofumi Tsubouchi; Jun Sakata; Seiichi Kato; Shiro Suzuki (Elsevier, 2021)
Ewing's sarcoma family tumors of the uterine cervix are extremely rare and, thus, an optimal treatment strategy has not yet been established. To the best of our knowledge, 28 cases were reported in the English literature between 1996 and 2020, and treatments involved surgery, neoadjuvant chemotherapy, adjuvant chemotherapy, and radiotherapy. The vincristine, doxorubicin, cyclophosphamide, ifosfamide, and etoposide (VDC-IE) protocol increased the survival rate of patients with non-metastatic Ewing's sarcoma family tumors. We herein present a case of a Ewing's sarcoma family tumor of the cervix in a one-month postpartum woman treated with neoadjuvant chemotherapy using the VDC-IE protocol and radical hysterectomy followed by adjuvant chemotherapy, and discussed the diagnosis and treatment of this tumor through a literature review.